ANALISIS KESIAPAN IMPLEMENTASI STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL MENENGAH PADA UMKM DI KOTA PONTIANAK - Septiani, Rizki Amelia; Jaurino (Jurnal Akuntansi, Auditing dan Investasi, 2022)
This study is entitled "Analisis Kesiapan Implementasi Standar Akuntansi Keuangan Entitas MikroKecil Menengah (SAK EMKM) Pada UMKM di Kota Pontianak" this study aims to see thereadiness of UMKM entrepreneur in implementing SAK EMKM published on January 1, 2018replacing its predecessor SAK ETAP. SAK EMKM is considered simpler so that it can reach UMKMentrepreneur. This research was conducted by distributing questionnaires to UMKM entrepreneurin Pontianak City. The indicators used include the issuance of SAK EMKM, the drafting system, theconcept of business entities, and adequate human resources. Of the 19 questionnaires that returned,there were 3 UMKMs that had prepared financial statements in accordance with SAK EMKM andthe rest did not meet the indicator requirements in readiness to implement SAK EMKM.